Foreign official purchases of U.S. treasuries and mortgage rates. Issue 16 (20th September 2019) - Fang, Jing; Liu, Dingming
ABSTRACT: This paper investigates the effects of foreign official purchases of U.S. treasuries on mortgage rates from January 1985 to June 2007 using a proxy structural vector autoregression (SVAR) model, where shocks to foreign official inflows to treasuries are identified by their correlation with foreign exchange interventions. Although mortgage rates significantly decrease in response to positive shocks to foreign official purchases of U.S. treasuries, these shocks only explain a small fraction of the variation in the U.S. mortgage rate.